Silencing of lncRNA CHRM3-AS2 Expression Exerts Anti-Tumour Effects Against Glioma via Targeting microRNA-370-5p/KLF4 - Wang, Dong; Chen, Qiang; Liu, Jun; Liao, Yuqing; Jiang, Qiuhua (Frontiers in Oncology, 2022)
Objectives Long non-coding RNAs (lncRNAs) are key regulators involved in the progression of glioma, and many functional lncRNAs are yet to be identified. This study aimed to explore the function of CHRM3-AS2, a rarely reported lncRNA, in glioma, as well as the underlying mechanisms involving miR-370-5p/KLF4. Methods Differentially expressed RNAs (DERs) were screened from two gene expression profiles of glioblastoma (GBM). Fluorescence in situ hybridisation was performed to determine the subcellular localisation of CHRM3-AS2. Cell viability, colony formation, apoptosis, migration, and invasion were evaluated using cell counting kit-8, colony counts, flow cytometry, wound healing, and Transwell assays, respectively. mRNA and protein expression of specific genes were measured using quantitative real-time polymerase chain reaction and western blotting, respectively. Dual luciferase reporter gene, RNA immunoprecipitation, and RNA pull-down assays were performed to identify the target relationships. A mouse xenograft model was established for in vivo validation. Results CHRM3-AS2 was screened as a prognosis-associated DER in GBM. CHRM3-AS2 expression was up-regulated in glioma cells, and CHRM3-AS2 was localised in the cytoplasm. Silencing of CHRM3-AS2 expression inhibited cell viability, colony formation, migration, and invasion and promoted apoptosis of U251 and SHG-44 cells. In addition, CHRM3-AS2 targeted miR-370-5p/KLF4 in glioma cells. The anti-tumour effect of CHRM3-AS2 silencing was weakened by miR-370-5p silencing or KLF4 overexpression. In vivo, silencing of CHRM3-AS2 expression inhibited tumour growth and Ki67 expression in mice. Overexpression of KLF4 also weakened the anti-tumour effect of CHRM3-AS2 silencing in mice. Conclusions Silencing of CHRM3-AS2 expression inhibited the malignant progression of glioma by regulating miR-370-5p/KLF4 expression.